Optimal quantity, location and capacity allocation of the additional renewable energy stations in a large-scale district heating system and comprehensive case analyses. (15th May 2023) - Wang, Jinda; Jin, Yufei; Zheng, Jinfu; Xue, Puning; Sun, Chunhua
Highlights: Introducing distributed RESs in an existing DHS has a great energy-saving potential. Two independent optimization modules are integrated to approach the optimal results. Virtual split method is proposed to simplify the operating optimization of DHS. Genetic algorithm is used to ensure the reliability and accuracy of the optimization. Abstract: Integrating the combined heat and power (CHP) plants with distributed renewable energy stations (RESs) is an important way to promote the low-carbon development of district heating system (DHS) and to further achieve "carbon neutrality" goal in the future. However, when the total capacity of power-to-heat devices is determined by district energy planning, different configurations (quantity, location, and installed capacity allocation) of additional RESs show various energy-saving potential in the long-term operation of DHS. In this study, an integrated optimization model consisting two independent optimization modules is proposed, aiming at maximizing the comprehensive economic benefits of distributed RESs. A novel virtual split method is also introduced to simplify the operating optimization of DHS. In addition, to ensure the reliability and accuracy of optimization calculation, a heuristic optimization tool (genetic algorithm) is applied to solve these non-linear optimization problems. Case studies from a real trans -regional DHS indicate that a reasonable configuration of additional RESs optimizes and equalizes the distribution of pressure and flow in the primary DHN, and the heat dissipation of flow energy in regulating valves and transmission pipelines can be reduced considerably. The proposed integrated optimization model and its solving processes can be migrated to other similar projects worldwide.